A Review on Localization Strategies in Wireless Sensor Networks using Beacon nodes - Panda, Sucheta; Priyadarshini, Sushree Bibhuprada B (International Journal of Computer Sciences and Engineering, 2026)
An abstract is a short summary of your research paper, usually about a paragraph (150-300 words) long. A well-written abstract can let readers get the essence of your paper, prepare readers to follow the detailed information, analyses, and arguments in your full paper, and help readers remember the key points. Note: -Special symbols, mathematical formulas, and equations are not allowed in the "Abstract" section. References should not be cited in the abstract.